Utilization of SLS-provided literature in PCARRD research proposals and terminal reports a citation analysis with implications for PCARRD scientific literature services - Quimsing, Loreta B.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1987)
The information use behavior of the agricultural researchers within the Philippine Council for Agriculture and Resources Research and Development (PCARRD) network was studied using citation analysis as a means of evaluating the usefulness of the Scientific Literature Service-provided information sources.
Sample citations from 73 research proposals and 75 terminal reports submitted from 1974-1982 by the ten research centers were used in this study. The ten research centers involved in this study include the Bicol Agriculture and Resources Research Consortium (CLARC), Cagayan Valley Integrated Agricultural Research System (CVIARS), Highland Agricultural Research Center (HARC), Ilocos Agricultural Research Center (ILARC), La Granja Agricultural Research Center (LGARC), Northern and Central Mindanao Coordinated Agriculture and Resources Research Program (NOCEMCARP), Palawan Agricultural Research Center (PARC), Southern Mindanao Agricultural Research Center (SMARC), and Visayas Coordinated Agricultural Research Program (VICARP). The citations were analyzed by form of literature used, recency of literature and the place of origin whether local or foreign.
Citation analysis showed that SLS is useful to agricultural researchers especially to those who are geographically remote from big libraries. Chi-square test analysis showed that there is very highly significant difference at 0.001 level among the ten centers with regards to the number of SLS-provided materials. CVIARS and SMARC tended to cite more SLS-provided materials than other centers in proportion to the total cited references.
Significant differences were also observed in the use of the different types of publications with, in general, marked preference for grey literature over periodical articles and books. The ten centers tended to show that foreign sources were more frequently cited than local ones.
Analysis of the recency of researchers' cited references definitely showed that they prefer more recent literature. Usage decreases with age of information.
Mimeographed.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Philippine Council for Agriculture and Resources Research and Development; Infomation services -- Use studies; Scientific literature -- Evaluation